2022
DOI: 10.3390/axioms11060293
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation of the Exponentiated Pareto Distribution Using Ranked Set Sampling and Simple Random Sampling

Abstract: In this paper, we have considered that ranked set sampling is able to estimate the parameters of exponentiated Pareto distribution. The method with which the maximum likelihood estimators for the parameters of exponentiated Pareto distribution is studied is numerical since there is no presence or possibility of a closed-form at the hands of estimators or any other intellectual. The numerical approach is a well-suited one for this study as there has been struggles in achieving it with any other technique. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…La población objetivo de este estudio está compuesta por mujeres cabeza de hogar que trabajan en el sector informal de la Avenida Oriental, ubicada en la comuna 10 de Medellín. La muestra fue seleccionada de forma aleatoria simple (Khamnei et al, 2022;Ozturk et al, 2023) durante un recorrido en el sector, utilizando una estratificación para asegurar la representatividad. Se respetó la confidencialidad y privacidad de la información proporcionada por las participantes, evitando cualquier divulgación que atente contra su integridad.…”
Section: Metodologíaunclassified
“…La población objetivo de este estudio está compuesta por mujeres cabeza de hogar que trabajan en el sector informal de la Avenida Oriental, ubicada en la comuna 10 de Medellín. La muestra fue seleccionada de forma aleatoria simple (Khamnei et al, 2022;Ozturk et al, 2023) durante un recorrido en el sector, utilizando una estratificación para asegurar la representatividad. Se respetó la confidencialidad y privacidad de la información proporcionada por las participantes, evitando cualquier divulgación que atente contra su integridad.…”
Section: Metodologíaunclassified
“….The natural logarithm of likelihood function (Ln LRSS) is given by (12) The first derivates of LnLRSS with respect to  and , respectively, are given…”
Section: Estimation Based On Rssmentioning
confidence: 99%
“…Al-Saleh and Al-Hadrami [7] used different set sizes for the RSS technique to estimate the mean of the normal and exponential distributions, and they found that this technique is more useful than SRS for estimating the mean of symmetric distributions. Khamnei and Mayan [8] estimated the parameters of the Gumbel distribution based on SRS and RSS when they compared the estimators of these two methods. Esemen and Gürler [5] estimated the parameters of the generalized Rayleigh distribution based on RSS and some of its modifications.…”
Section: Introductionmentioning
confidence: 99%